THE CLINICAL EFFICACY OF HYPOOSMOLYARNY ORAL SOLUTION WITH LACTOBACILLUS GG FOR REHYDRATION IN INTESTINAL INFECTIONS IN CHILDREN - V. F. Uchaikin; A. A. Novokshonov (LLC "Diagnostics and Vaccines", 2015)
In 60 patients with moderate forms of the OCI «osmotic» (76.7%) and «invasive» (23.3%) such as diarrhea, aged 3-12 years, to evaluate the clinical effectiveness, impact on water and electrolyte metabolism, acid-base balance and intestinal microbiocenosis hypoosmolyarny solution with Lactobacillus rhamnosus GG «Regidron Bio» (30 patients) and hyperosmolarny solution (30 patients). It was found that in the group of patients receiving «Regidron Bio», in contrast to the hyperosmolarny solution, is rapidly disappearing symptoms of intoxication and exsicosis, abdominal pain, meteorism and liquid watery diarrhea. The average duration of the acute period is reduced from 4,06 ± 0,32 to 3,07 ± 0,27 day (P < 0,05). Already by the end of the 1st day of the beginning of rehydration, almost all patients (90%) are normalized malformations of blood electrolytes and glucose, hematocrit, and on the 2nd day, which took place in 80% of patients with metabolic acidosis. The addition of the «Bio rehydron» Lactobacillus rhamnosus GG facilitates, unlike hyperosmolarny solution indicator normalizing lg Lactobacilli (in 73.3%) and Enterococci (93.3%), but has no significant positive impact on the amount of Bifidobacteria and Escherichia coli.